2019
DOI: 10.1103/physrevb.100.180407
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization-governed magnetoresistance anisotropy in the topological semimetal CeBi

Abstract: Magnetic topological semimetals, the latest member of topological quantum materials, are attracting extensive attention as they may lead to topologically-driven spintronics. Currently, magnetotransport investigations on these materials are focused on the anomalous Hall effect. Here, we report on the magnetoresistance anisotropy of topological semimetal CeBi, which has tunable magnetic structures arising from localized Ce 4f electrons and exhibits both negative and positive magnetoresistances, depending on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…shows the Kohler's plot obtained from the resistance R(T ) measured at various fields above 5 T, in the temperature range 1.8 K≤ T ≤ 10 K. The anisotropic MR behavior of CeBi was studied recently Lyu et al (2019), and it suggests a magnetization governed MR in the temperature regime ∼ 12.8 K -25 K. This is not inconsistent with our results. Whereas, they observe a magnetization dependent magnetoresistance in the temperature regime between T N /2 < T < T N , we focus on the Kohler's rule behavior below that and the shift to negative MR above that temperature region.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…shows the Kohler's plot obtained from the resistance R(T ) measured at various fields above 5 T, in the temperature range 1.8 K≤ T ≤ 10 K. The anisotropic MR behavior of CeBi was studied recently Lyu et al (2019), and it suggests a magnetization governed MR in the temperature regime ∼ 12.8 K -25 K. This is not inconsistent with our results. Whereas, they observe a magnetization dependent magnetoresistance in the temperature regime between T N /2 < T < T N , we focus on the Kohler's rule behavior below that and the shift to negative MR above that temperature region.…”
Section: Discussionsupporting
confidence: 82%
“…The relaxation technique is usually used for measurements below 100 K, as the relaxation times are smaller in that temperature range. CeBi, the heaviest member of the CeX family, is known to show multiple metamagnetic transitions in the magnetic field -temperature phase space, with a strong anisotropy arising from crystalline electric field (CEF) effects and a resultant anisotropic magnetoresistance Bartholin et al (1974Bartholin et al ( , 1979; Rossat-Mignod et al (1980; Kohgi et al (2000); Lyu et al (2019). It thus provides an exemplary candidate to study the effects of magnetic ordering in magnetoresistance and electronic structure.…”
Section: Heat Capacitymentioning
confidence: 99%
“…28,45,59,62,63 Interestingly, similar angular magnetoresistance occurs in ErBi owing to its weak anisotropic magnetization. 28 However, different cases emerge in the sister compounds with strong magnetic anisotropy, such as CeSb, 10 CeBi 64 and HoSb. 58 It is reported that their extra magnetoresistance minima in CeSb and CeBi occur when Ce Γ (1) 8 orbital flops 10,64 and extra magnetoresistance minima in HoSb appear when it undergoes a phase transition from ferromagnetic to HoP-type antiferromagnetic state and vice versa .…”
Section: Resultsmentioning
confidence: 99%
“…28 However, different cases emerge in the sister compounds with strong magnetic anisotropy, such as CeSb, 10 CeBi 64 and HoSb. 58 It is reported that their extra magnetoresistance minima in CeSb and CeBi occur when Ce Γ (1) 8 orbital flops 10,64 and extra magnetoresistance minima in HoSb appear when it undergoes a phase transition from ferromagnetic to HoP-type antiferromagnetic state and vice versa . 58 Here, except for the ones at ∼ n π/2, no other obvious magnetoresistance minima can be observed in PrBi.…”
Section: Resultsmentioning
confidence: 99%